ANALISIS KINERJA OPERASIONAL ANGKUTAN UMUM TRAYEK WARUNG POJOK - TUNJUNG TEJA - Telly Rosdiyani; Putri Aperia; Euis Amilia (Journal of Sustainable Civil Engineering (JOSCE), 2026)
Rural public transportation plays a vital role in supporting community mobility, particularly in areas with limited access to alternative transportation modes. However, the sustainability of rural public transport services faces various challenges, including operational efficiency, service quality, and competition from technology-based transportation services. This study aims to analyze the operational performance of rural public transportation on the Warung Pojok–Tunjung Teja route in Serang Regency based on cycle time, travel speed, service frequency, and headway indicators, as well as to identify user characteristics and perceptions regarding the services provided. A descriptive quantitative approach was employed, with data collected through field observations, operational surveys, interviews, and questionnaires distributed to 50 public transport users. The results indicate that the vehicle cycle time was 1.6 hours, the average travel speed reached 44 km/h, the service frequency was 10 vehicles per hour, and the average headway was 6 minutes. User characteristics were dominated by individuals aged 10–20 years (34%) and school students (34%), while the primary travel purpose was attending college or educational activities (40%). Furthermore, 44% of respondents reported having online transportation services as an alternative mode, indicating increasing competition from app-based transportation providers. In addition, 48% of respondents expressed the need for comprehensive service improvements, including lower fares, fleet rejuvenation, clear departure schedules, and extended operating hours. The findings suggest that rural public transportation on the Warung Pojok–Tunjung Teja route continues to play a significant role in supporting community mobility, particularly for educational and work-related activities. Therefore, improvements in service quality and operational management are required to enhance the competitiveness and sustainability of rural public transportation services.